Design and analysis light weight lift system for disable people - Siti Fatimah, Ismail (2008)
Lift is a kind of system in building to move people vertically. In Malaysia, most of the lifts in the buildings are available only five levels and above thus the movement of disable people below than five levels are limited. So, the idea of design and analysis of light weight and lift system for the use of disable people is developed. Disable people subjected for whom using wheelchair or more specifically people walking is difficult or impossible due to mental or physical illness, injury, or disability to move. The aim of design is transporting a disable people using wheelchair from ground floor to first floor. Design concept of lift is based on rails, electric motor and gears. A suitable rail, electric motor and gear have considered in this design. Another part of lift design is platform and space requirement of platform depend on space of wheelchair and capacity of lift design. All components have been selected in order to design reliable lift system. The structural and component model of lift will be developed using the SOLIDWORKS software. The three-dimension solid model is then imported to the ALGOR and COSMOS software to an analysis on the sustainable and movement of the lift system